2022
DOI: 10.1111/jdi.13865
|View full text |Cite
|
Sign up to set email alerts
|

Continuous glucose monitoring system profile of women diagnosed as gestational diabetes mellitus by International Association of Diabetes and Pregnancy Study Groups criteria and labeled as normoglycemic by alternate criteria in early pregnancy

Abstract: Aims/Introduction: We aimed to evaluate and compare continuous glucose monitoring system (CGMS)-based glycemic parameters in women in early pregnancy (<20 weeks of gestation) who were classified as: (i) gestational diabetes mellitus (GDM) by the International Association of Diabetes and Pregnancy Study Groups (IADPSG), but normoglycemia by alternate (UK National Institute for Health and Care Excellence, Canadian Diabetes Association and Diabetes in Pregnancy Study group of India) criteria; and (ii) normoglycem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…There is no standard CGM-based glucose range for normoglycemic pregnancies; recommendations for glucose levels using CGM are mainly based on studies of participants with type 1 diabetes 11. In one study of 58 normoglycemic participants between gestational age 8 and 20 weeks, CGM data for up to 72 hours showed a per cent time 63–140 mg/dL (3.5–7.8 mmol/L) of 98.2% 12. Another study used a matched control group based on age, parity and BMI (no GDM), and found a per cent time 63–140 mg/dL (3.5–7.8 mmol/L) of 96.1%, 95.9% and 93.5% in trimesters one, two and three, respectively, among those without GDM 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no standard CGM-based glucose range for normoglycemic pregnancies; recommendations for glucose levels using CGM are mainly based on studies of participants with type 1 diabetes 11. In one study of 58 normoglycemic participants between gestational age 8 and 20 weeks, CGM data for up to 72 hours showed a per cent time 63–140 mg/dL (3.5–7.8 mmol/L) of 98.2% 12. Another study used a matched control group based on age, parity and BMI (no GDM), and found a per cent time 63–140 mg/dL (3.5–7.8 mmol/L) of 96.1%, 95.9% and 93.5% in trimesters one, two and three, respectively, among those without GDM 9.…”
Section: Discussionmentioning
confidence: 99%
“… 11 In one study of 58 normoglycemic participants between gestational age 8 and 20 weeks, CGM data for up to 72 hours showed a per cent time 63–140 mg/dL (3.5–7.8 mmol/L) of 98.2%. 12 Another study used a matched control group based on age, parity and BMI (no GDM), and found a per cent time 63–140 mg/dL (3.5–7.8 mmol/L) of 96.1%, 95.9% and 93.5% in trimesters one, two and three, respectively, among those without GDM. 9 The CGM-based glucose ranges observed in this study may be representative of glucose levels in all trimesters of uncomplicated pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…With this background, this study aims to evaluate whether the continous glucose monitoring system (CGMS) profile of women with isolated mild FPG elevation (5.1-5.5 mmol/L or 92-99 mg/dL), isolated post-load plasma glucose elevation [1 h C 10.0 mmol/L (180 mg/dL) or 2 h C 8.5 mmol/L (153 mg/dL)], or both are different from those with normoglycemia defined using WHO criteria. We have used a CGMS-derived dataset from our previous studies to answer these objectives [10,11]. Briefly, in these studies, we reported: (a) differences in CGMS profile between women with normoglycemia and early GDM per IAPDSG/WHO 2013 criteria [10], and (b) differences in CGMS profile between women with normoglycema and early GDM by IADPSG/WHO 2013 criteria but normoglycemia defined by alternative criteria [NICE, Canadian Diabetes Association (CDA) and Diabetes in Pregnancy Study Group of India (DIPSI)] [11].…”
Section: Introductionmentioning
confidence: 99%
“…We have used a CGMS-derived dataset from our previous studies to answer these objectives [10,11]. Briefly, in these studies, we reported: (a) differences in CGMS profile between women with normoglycemia and early GDM per IAPDSG/WHO 2013 criteria [10], and (b) differences in CGMS profile between women with normoglycema and early GDM by IADPSG/WHO 2013 criteria but normoglycemia defined by alternative criteria [NICE, Canadian Diabetes Association (CDA) and Diabetes in Pregnancy Study Group of India (DIPSI)] [11]. The data emerging from the current study would help to delineate the significance of a milder degree of FPG elevation in early pregnancy and of post-load plasma glucose values derived from a 75 g OGTT as well as the appropriateness of using higher isolated FPG thresholds (5.6-6.9 mmol/L or 100-125 mg/dL) for the diagnosis of GDM in early pregnancy.…”
Section: Introductionmentioning
confidence: 99%